Colonial Legacy and Self-Discovery in Nayantara Sahgal’s A Time To Be Happy: A Postcolonial Reading (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Nayantara Sahgal’s A Time To Be Happy portrays the unsteady atmosphere of post-independence India, where political freedom has been achieved but the deeper impact of colonial rule continues to change society. Set in the fictional town of Sharanpur, the novel depicts a society caught between holding on to the past and adapting to change. Colonial influence can still be seen not just in economic systems and class differences but also in people’s ambitions, education, and even in how they view themselves and others. Issues like gender inequality and strong patriarchal norms further show that independence did not bring complete social change. Drawing on insights from major postcolonial theorists such as Edward Said, Homi K. Bhabha, Frantz Fanon, and Gayatri Chakravorty Spivak, this study argues that Sahgal presents independence not as a complete break but as an ongoing process of negotiation, where colonial legacy continues to influence institutions, attitudes, and personal identity.